Artificial Intelligence Adoption and Psychological Wellbeing among Some Selected Employees of Technology-Driven Organization in Accra - Luguyare, S. (University of Ghana, 2025)
The study investigates the relationship between Organizational AI adoption and Psychological Well-Being (PWB). It also explores how some demographic factors (age and gender) moderate the relationship between AI adoption and psychological well-being, as well as views employees have towards AI adoption and potential challenges/effects of the adoption of AI in Greater Accra, Ghana. The Job Demands-Resource (JD-R) and Technology Acceptance Models (TAM) were used as underpinning theories for this study. Using an explanatory sequential mixed-method approach, a total of 202 participants (Quantitative= 189 and Qualitative= 13) were purposively sampled for this study. In Study 1, a regression analysis showed a positive relationship between AI adoption and PWB among technology-driven employees of Ghana. Personal growth predicted AI adoption than the other dimensions of PWB, although modestly. A hierarchical regression analysis was conducted to test how demographic factors (Gender, Age) affect AI adoption. Gender and Age did not moderate the relationship between AI adoption and PWB. In Study 2, participants expressed mixed-feelings viewing AI as a helpful challenge. Two sub-themes emerged from these mixed feelings (positive and negative sentiments) offering an understanding of the views held about AI adoption. Four key challenges/effects of AI adoption -Reduced interaction, unemployment, feelings of inadequacy, digital stress-emerged from the study. From this study, AI is seen as a helpful collaborator but with some potential challenges to employee wellbeing. The researcher recommends more advocacy on AI adoption in Ghana while prioritizing psychological interventions that could mitigate associated potential challenges. Study findings were integrated and discussed in line with theory and literature.
MPhil. Industrial and Organizational Psychology
Keywords: AI adoption a; Psychological Well-Being (PWB; Organizational; Ghana